Developments of Islam in Southeast Asia - Wahid, Abdurrahman (The Indonesian quarterly, 1986)
The essay outlines current developments among SE Asian Muslims as a whole, the impact of those developments on the region at large and the projection of Islam's future in Indonesia and Malaysia. The development of Islam in Java contrasted with this development among the Minangkabau people. (DÜI-Sen)